Kappa opiate receptors localized by autoradiography to deep layers of cerebral cortex: relation to sedative effects. - Goodman, R R (1982)
Kappa opiate drugs differ from other opiates in their unique sedative actions and lack of cross-tolerance. We have visualized kappa opiate receptors by in vitro autoradiography using the kappa drugs [3H]ethylketazocine ([3H]EKC) and [3H]bremazocine. Though these ligands also label mu and delta opiate receptors, their binding is rendered kappa specific by coincubation with morphine and [D-Ala2, D-Leu5]enkephalin (DADL-Enk) to displace mu and delta interactions, respectively. Labeling patterns with [3H]EKC and [3H]bremazocine are the same and differ markedly from localizations of mu and delta opiate receptors visualized with [3H]dihydromorphine and [3H]DADL-Enk, respectively. The highest density and most selective localization of putative kappa receptors occurs in layers V and VI of the cerebral cortex. In these layers cells are localized which project to the thalamus regulating sensory input to the cortex. Receptors in these layers could account for the unique sedative and possibly analgesic effects of kappa opiates.